Intrathoracic gastric perforation secondary to corrosive ingestion: a rare complication - Arora, Richa (Quant Imaging Med Surg, 2016)
This case report describes a rare and serious case of acid ingestion in a 50-year-old man who developed necrosis and perforation of gastric fundus and diaphragm with extension of air and fluid collection in the thorax. To the best of our knowledge, this complication has not been described so far in the literature.